Figur Intelektual Muslim dalam Qur’an: Tafsir Tematik Terhadap Kata Ulul Albab - Ahmad Dibul Amda (AL QUDS : Jurnal Studi Alquran dan Hadis, 2020)
The main issues addressed in this study are the meaning and nature of the word Ulul Albab in the Qur’an. In general, some theories say that Ulul Albab means a person who has intelligent thoughts, conscious heart, who is opened and understand the essence beyond the physical nature. The word also refers to one who enjoys what he sees and knows, and who always remembers Allah The Almighty through all things he sees and touches. Those meaningsare similar to the meaning of the term “Intellectual” in the general senseknown bynowadays people. So, can the term Ulul Albab be translated into “Intellectual Muslim”?, and how is then the Qur’anic conception of Ulul Albab’s existences and characteristics?Thus, this study deals with the meanings and essence of Ulul Albab in the Qur’an, the characteristics of Ulul Albab, and how to build Ulul Albab characteristics properly? This is a library research. The data analysis used content analysis on the material object in the form of verses of the Qur’an by using Thematic Interpretation Method approach الـتـفــســيــرالمــوضــوعـى))  (al-Tafsir al-Maudhu’i) as a formal object, and supported by some relevant theories. The objective of this research is to find out the valid and concrete data or theories about the meanings and nature of Ulul Albab  in the Qur’an. This research results in several conclusions that; the term Ulul Albab in the Qur’an has the same meaning as the term “Intellectual Muslim”, Al-Qur’an describes several characteristics of Ulul Albab and how to build and developed the mentioned characteristics